The Earlier the Better: Structural Analysis and Separation of Lanthanides with Pyrroloquinoline Quinone. Issue 44 (7th July 2020) - Lumpe, Henning; Menke, Annika; Haisch, Christoph; Mayer, Peter; Kabelitz, Anke; Yusenko, Kirill V.; Guilherme Buzanich, Ana; Block, Theresa; Pöttgen, Rainer; Emmerling, Franziska; Daumann, Lena J.
Abstract: Lanthanides (Ln) are critical raw materials, however, their mining and purification have a considerable negative environmental impact and sustainable recycling and separation strategies for these elements are needed. In this study, the precipitation and solubility behavior of Ln complexes with pyrroloquinoline quinone (PQQ), the cofactor of recently discovered lanthanide (Ln) dependent methanol dehydrogenase (MDH) enzymes, is presented. In this context, the molecular structure of a biorelevant europium PQQ complex was for the first time elucidated outside a protein environment. The complex crystallizes as an inversion symmetric dimer, Eu2 PQQ2, with binding of Eu in the biologically relevant pocket of PQQ. LnPQQ and Ln1Ln2PQQ complexes were characterized by using inductively coupled plasma mass spectrometry (ICP‐MS), infrared (IR) spectroscopy, 151 Eu‐Mössbauer spectroscopy, X‐ray total scattering, and extended X‐ray absorption fine structure (EXAFS). It is shown that a natural enzymatic cofactor is capable to achieve separation by precipitation of the notoriously similar, and thus difficult to separate, lanthanides to some extent. Abstract : No co‐ligands required : The precipitation and solubility behavior of lanthanide complexes with pyrroloquinoline quinone (PQQ), is presented. Complexes with early lanthanides are preferentially formed with PQQ and rapidly precipitate out of aqueous solutions. The first molecular structure of a biorelevant europium PQQ complex outside a protein environment is reported and shows a Eu2 PQQ2 dimer.